2018
DOI: 10.3390/foods7090135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional and Technological Attributes of Whole Wheat Based Bread Fortified with Chia Flour

Abstract: The aim of this study was to investigate and compare the effect of wheat bread fortification with varied levels (2%, 4%, and 6%) of chia seed powder (full fat) and cakes (defatted, residue after oil extraction). Chia flour was added to whole wheat bread rich in vital wheat gluten for the first time. The breadcrumbs were assessed for their antioxidant activity, nutritional content, textural properties, color, and sensory profiles. The addition of chia seed powder, particularly in high levels, was more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
6
25
1
Order By: Relevance
“…It was found that all the tested bread additives increased the antioxidant potential against DPPH free radical scavenging (Figure b). This is consistent with the studies carried out by Sayed‐Ahmad et al (), which showed that the addition of chia seed and cake improved the antioxidant activity of wheat bread. In other research the addition of lettuce flour, which is rich in antioxidant polyphenols, promoted an increase in bread phenolic content and antioxidant activity (Plazzotta et al, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that all the tested bread additives increased the antioxidant potential against DPPH free radical scavenging (Figure b). This is consistent with the studies carried out by Sayed‐Ahmad et al (), which showed that the addition of chia seed and cake improved the antioxidant activity of wheat bread. In other research the addition of lettuce flour, which is rich in antioxidant polyphenols, promoted an increase in bread phenolic content and antioxidant activity (Plazzotta et al, ).…”
Section: Resultssupporting
confidence: 93%
“…There were no significant differences between the lightness of the gluten‐free bread and wheat bread and those supplemented with P1 and P2 wastes. The darkening of the bread crumb color induced by the addition of chia seed flour was observed by Steffolani et al () and Sayed‐Ahmad et al () as well. The values of parameter a * in the supplemented crumb samples increased significantly in comparison with that of the control in the case of both the wheat and gluten‐free breads.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The gum present in chia seed has the ability to hold water and oil as well as having emulsifier and stabilizer potential (Segura-Campos, Ciau-Solís, Rosado-Rubio, Chel-Guerrero, & Betancur-Ancona, 2014). Furthermore, chia seed when added to wheat bread increases its antioxidant activity, nutritional content, textural properties (higher moisture content and lower hardness), color, and sensory profiles with 3.7 points in global acceptability score (1 to 5) (Sayed-Ahmad et al, 2018). Similarly, the use of 10% of chia flour in gluten-free bread received an overall acceptability scores of 8.1 on a 10 cm scale, and increased the levels of lipid, protein and dietary fiber in comparison with white gluten-free bread (Sandri, Santos, Fratelli, & Capriles, 2017).…”
Section: Chia Seed Usesmentioning
confidence: 99%
“…The Texture analyzer is equipped with a load cell of 100 N. Cylindrical probe of 35 mm diameter was used at a test speed of 1 mm/s and trigger force: 9.8 N. The samples were Compressed to an extent of 48%. All values aregiven as an average of three measurements and the total texture change were evaluated[23].…”
mentioning
confidence: 99%